Cytological spectrum of lymph node lesions in fine needle aspiration cytology - Gupta, Deepti; Goswami, Sumeet; More, Sarika (International Journal of Research in Medical Sciences, 2023)
Background: Fine needle aspiration cytology (FNAC) is becoming preoperative method of choice for diagnosis and management of various lumps and lesions since few decades. It helps clinician to decide mode of treatment in most cases in both non-neoplastic and neoplastic disorders. As cervical, axillary and inguinal lymphadenopathies are commonly encountered clinical problems, in this study, we evaluated the utility of FNAC for assessment of lymphadenopathy. Methods: This was a retrospective observational study done during the period between January 2016 to December 2019 in a private laboratory centre affiliated with private multispeciality hospital in Bhopal Madhya Pradesh. The FNAC procedure was done without radiological guidance for palpable lymph nodes of cervical, axillary, and inguinal regions. 10ml syringe and 23/24-gauge needles were used along with a plunger for FNAC procedure. Smears were made by standard smearing technique. Slides were stained with Papanicolaou (PAP), Lieshman and Giemsa stain and Diff-Quik methods. Ziehl-Neelson (ZN) staining for acid fast bacilli was done wherever required. Results: Total 128 cases of lymphadenopathy were assessed. Cervical lymph nodes were most commonly (77.3%) involved and reactive lymphadenitis (34.3%) was most common diagnosis on FNAC. Tubercular lymphadenitis was most common in young adults and reactive nonspecific lesions were most common in paediatric group. Metastatic carcinomas were most common after 50 years age group. Conclusions: Fine needle aspiration is simple, rapid and cost-effective method to know the cause of lymphadenopathy and also a reliable method to categorize the cause of lymphadenopathy into reactive, inflammatory, metastatic, and lymphoproliferative, avoiding the necessity of biopsy.